PENGEMBANGAN POTENSI DAN KREATIVITAS PEMUDA MELALUI WORKSHOP PENULISAN KREATIF: The Development of Youth Potential and Creativity through Creative Writing Workshop - Sari, Norma Atika; Natsir, M.; Suhendi, Indrawan Dwisetya; Muhajir, Fatimah (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2022)
Abstract: The main focus of this creative writing workshop activity is to recognize the potential of literary writing talents that exist in young people (students). In addition, this workshop also aims to ignite the creativity and innovation of the participants. The location of the workshop was held in Kutai Lama, Anggana Sub-district, Kutai Kartanegara on 19 - 22 June 2022. The activity plan consisted of: (1) distribution of questionnaires, (2) presentation of workshop material by trainers, (3) question and answer session (discussion with participants), and (4) creative writing practice by creating collaborative story fragments. At the end of the activity, many participants did not realize that there was potential for writing talent within them. Participants were also given a new perspective on the benefits of reading and writing literary works in exercising the power of imagination and creativity that are useful in almost all aspects of life. Keywords: creative writing; student; potential; creativity.   Abstrak: Fokus utama kegiatan workshop penulisan kreatif ini adalah mengenali potensi bakat menulis sastra yang ada di dalam diri pemuda (pelajar dan mahasiswa). Selain itu, workshop ini juga bertujuan memantik kreativitas dan inovasi para peserta. Lokasi workshop dilaksanakan di Kutai Lama, Kecamatan Anggana, Kutai Kartanegara pada tanggal 19 - 22 Juni 2022. Rancangan kegiatan berupa : (1) pembagian kuesioner, (2) pemaparan materi latihan oleh narasumber, (3) sesi tanya jawab dan diskusi dengan peserta, serta (4) praktik menulis kreatif dengan menciptakan fragmen cerita kolaboratif. Di akhir kegiatan banyak peserta yang sebelumnya tidak menyadari bahwa ada potensi bakat menulis dalam diri mereka. Peserta juga diberi pandangan baru tentang manfaat membaca dan menulis karya sastra dalam melatih daya imanijasi dan kreativitas yang berguna dalam hampir segala aspek kehidupan. Kata kunci: penulisan kreatif; pelajar; mahasiswa; potensi; kreativitas.